PENCEGAHAN HIPERKOLESTEROLEMIA DAN PENURUNAN RESIKO PENYAKIT JANTUNG DENGAN MENGKONSUMSI MINUMAN KESEHATAN - Muharni; Yohandini, Heni; Ferlinahayati; Julinar (Jurnal Abdi Insani, 2024)
Indralaya Mulya is one of the sub-districts in Indralaya District, Ogan Ilir, South Sumatra, about 6 KM from the Sriwijaya Indralaya University campus. In modern life, people's lifestyles tend to be unhealthy due to consuming foods that contain high fat, consuming less vegetables and fruit and relatively lacking sports activities. This will trigger high cholesterol (hypercholesterolemia). Various complications can be caused by high levels of cholesterol in the blood, including heart disease. Considering that the condition of high cholesterol levels is commonly found in society, the public has been introduced to the prevention of hypercholesterolemia and reducing the risk of heart disease by consuming health drinks. In this activity, socialization was carried out on the use of traditional medicinal plants (curcuma, guava leaves, sweet starfruit and green betel leaves) to prevent hypercholesterolemia. Furthermore, activity participants' cholesterol levels were also checked. The results of the activity show that the public has great curiosity about the use of medicinal plants to lower cholesterol, the public is relatively aware of the impact of hypercholesterolemia. The results of checking cholesterol levels showed that the participants (20 people) had cholesterol levels in normal conditions. Based on this activity, it was concluded that the people of Indralaya Mulya were relatively in good health and had a high level of concern about maintaining their health.